STUDI ETNOBOTANI DALAM BUDAYA KULINER MELAYU RIAU DI KABUPATEN SIAK DAN UJI FITOKIMIA - Supriani, Susi; ', Fitmawati; Sofiyanti, Nery (Jurnal Online Mahasiswa (JOM) Bidang Matematika dan Ilmu Pengetahuan Alam, 2014)
Ethnobotany is the study of human and plant relationships such as the use of plants in culinary. However, the study of culinary herb in Indonesia including Siak, Riau Province, is still limited. The purposes of this research were to identify the plant species used in Siak Culinary and to test their phytochemical compounds. This research was conducted from Desember 2013 to Februari 2014. The sampling method used in this study was the purposive sampling method. All of the main plants used in Siak culinary were tested for their phytochemical compounds. The results showed that a total of 49 species were used in Siak Culinary, 31 species were cooked before being consumed while 18 species were freshly consumed. The phytochemical test showed that 16 species contained alkaloid, 14 species contained flavonoid, 41 species contained saponin, and 24 species contained tanin.